Evaluation of the Anterior Cruciate Ligament Injury Risk During a Jump-Landing Task Using 3-Dimensional Kinematic Analysis Versus the Landing Error Scoring System. - Morooka, Takatoshi; Yoshiya, Shinichi; Tsukagoshi, Rui; Kawaguchi, Kotaro; Fujioka, Hiroyuki; Onishi, Shintaro; Nakayama, Hiroshi; Nagura, Takeo; Tachibana, Toshiya; Iseki, Tomoya (Orthopaedic Journal of Sports Medicine, 2023)
Background: The Landing Error Scoring System (LESS) has been utilized on the field or in the clinic to identify patients with an increased risk for anterior cruciate ligament (ACL) injuries; however, its validity and efficacy have not been fully confirmed. Purpose: To assess the efficacy of the LESS in identifying the ACL injury risk by examining the correlation between the LESS score and motion patterns on 3-dimensional kinematic analysis. Study Design: Controlled laboratory study. Methods: The jump-landing motion was analyzed for 16 female basketball or badminton players who volunteered to participate in the study. All study participants were aged 19 or 20 years. The sequence of motion was evaluated with the LESS, while kinematic data were simultaneously acquired with a 3-dimensional motion analysis system utilizing the point cluster method. The correlation between the LESS score and knee kinematics was statistically analyzed. Results: When a LESS score ≥6 was defined to be a risk factor for ACL injuries, 7 of the 16 participants (43.8%) were found to exhibit risky motion patterns. Significant correlations were noted between the LESS score and knee valgus (r = 0.87; P <.0001) and internal tibial rotation (r = 0.57; P =.02) at landing. By contrast, a substantial variability was present in knee flexion, showing no correlation with the LESS score. Conclusion: Significant correlations were found between the LESS score and knee valgus and internal tibial rotation during a jump-landing task. Clinical Relevance: The LESS can be regarded as an effective measure to identify risky motion patterns that may increase the likelihood of ACL injuries.